Necessidade de tipificação penal da alienação parental e a aplicação da lei de n.12.403/2011 - Araújo, Susana Vieira de (2013)
This paper addresses the issue of the necessity of criminal definition of parental alienation and the applicability of Law No. 12403/11 which reflects the whole constitution of parental alienation scored within these institutions, penal and criminal procedure. This sale, which is materialized through a dispute between the custodial parent and the other parent, so that those who hold the guard uses the children to avenge the parent who has visitation rights by disparaging campaigns, as not only accept the end of the marriage relationship. Reflecting this also with relatives, extending to the grandparents. With the privilege of studying this phenomenon, as well as the possibility of loss of power due to the same family, is that goes through a brief history of the family and some institutes which refer to the relationship parents and children, as the family power and procedural practices, this finding solutions to concrete cases. With the completion of multidisciplinary studies, done by professionals specialized area of law, together with psychologists, social workers and doctors is that one can give solution to this case, even prevent its effects. The technical reports arising from these studies underlie the decisions of the judiciary. This time, the loss of family power reflects a necessity imposed upon alienating in the face of parental alienation. After the tort approach, the approach is punitive, so that portrays the possibility of application of Law No. 12403/11 showing that precautionary measures are effective measures against the criminal actions of the alienating parent. This law put to the detention as an exception, is consistent with the reasons for the veto of Article 10 of the law of parental alienation. The application also institute criminal transaction, proposed in the rite of Law n º 9099/95 fits perfectly, too, to compel parental alienation. Demonstrating, categorically, that the criminalization of parental alienation avoid the growing characterization of this institute in Brazilian families. The work is characterized by a bibliographical information obtained through the sources of jurisprudence, doctrinal and Laws.